The Effect Of Lemon Oil Aromaterapy Inhalation On Emesis Gravidarum In Trimester Pregnant Women I - rinda Lamdayani (International Journal of Health Science and Technology, 2021)
Nausea and vomiting in pregnancy causes the mother to become weak, pale, and decrease body fluids. Lemon oil is one of the herbal oils that is considered a safe drug in pregnancy, according to a study 40% of women used lemon aromatherapy to relieve nausea and vomiting and 26.5% reported being effective for controlling nausea and vomiting symptoms. This study was to determine the effect of inhalation of lemon oil aromatherapy on emesis gravidarum in first trimester pregnant women. By using the literature study method, an analysis was carried out on the results of searching journals and articles with a review of existing theories. This study revealed that there was an effect of giving inhaled lemon aromatherapy on morning sickness in pregnant women.